ORDOVICIAN TYPE MUD MOUNDS IN THE "DIKARI UNIT" OF THE BABINO LIMESTONE QUARRY - Dronov P.V.; Early A.V. (My University, 1998)
Detailed description of the two newly discovered Hecker-type mud mounds from the Babino quarry is given. A complex multistory internal structure of one of the buildups is well established. The main stages of development are coeval in both mounds.
Keywords: Ordovician; Paleozoic::Ordovician; Палеозой::Ордовикская